Derivation of Adipocytes from Human Endometrial Stem Cells (EnSCs) - Ai; AR Shahverdi; S Ebrahimi Barough; H Mohseni Kouchesfehani; S Heidari; R Roozafzoon; J Verdi; A Khoshzaban (JRI, 2012)
Background: Due to increasing clinical demand for adipose tissue, a suitable cell for reconstructive adipose tissue constructs is needed. In this study, we investigated the ability of Human Endometrial-derived stem cells (EnSCs) as a new source of mesenchymal stem cells to differentiate into adipocytes. EnSCs are the abundant and easy available source with no immunological response, for cell replacement therapy. Methods: Single-cell suspensions of EnSCs were obtained from endometrial tissues from 10 women experiencing normal menstrual cycles, and were cultured at clonal density (10 cells/cm2) or limiting dilution. Endometrial mesenchymal stem cell markers were examined flow cytometry. These cells were treated with adipogenic-inducing medium for 28 days. The adipogenic differentiation of the EnSC was assessed by cellular morphology and further confirmed by Oil Red O staining and RT-PCR. The BM-MSC differentiated into adipocytes in the presence of adipogenic stimuli for 3 weeks. Results: The flow cytometric analysis showed that the cells were positive for CD90, CD105, CD146 and were negative for CD31, CD34.We showed that the key adipocytes marker PPARa was expressed in mRNA level after 28 days post treatment (PT). Conclusion: According to our finding, it can be concluded that EnSCs represent a useful in vitro model for human adipogenesis, and provide opportunities to study the stages prior to commitment to the adipocyte lineage.
Keywords: Adipocyte cell, Differentiation, Endometrial stem cell